Arachnoiditis – A challenge in diagnosis and success in outcome – Case report - Saleh Safi; Abdelnaser Thabat; Mohamed Arshad; Mohamed Hanoun (Interdisciplinary Neurosurgery, 2021)
Background: Spinal arachnoiditis is an insidious disease caused by an inflammatory process of the arachnoid membrane resulting from many possible causes. Several factors such as spinal surgery, myelography, or infectious meningitis are known to cause adhesive arachnoiditis. Multiple studies proposed that the initial stage of syringomyelia in spinal arachnoiditis would be intramedullary cystic degeneration caused by ischemia due to circulatory disturbance in the pia-arachnoid. Disturbance of cerebrospinal fluid flow around the spinal cord has an important role in the development of syringomyelia due to spinal arachnoiditis. The presentation of spinal arachnoiditis depends on the level of the disease. For instance, Lumbar or lumbosacral adhesive arachnoiditis is usually related to lumbar disc diseases, and radicular pain due to involvement of the cauda equina is the main symptom. Our case represents a rare cause of arachnoiditis for a patient was presented with lower limb weakness and found to have extensive syringomyelia. Case description: 29-year-old male patient, presented with 3 days history of progressive lower limbs weakness. He had 3 months history of mild lower back pain and subjective left lower limb weakness. MRI showed extensive intramedullary hyperintense lesion extending from T3 to L1 with scattered post-contrast nodular enhancement. Diagnosis of arachnoiditis with syringomyelia done. The patient underwent Thoracic 8 laminectomy, arachnoid biopsy, and syrinx to subarachnoid space shunt. Tissue culture-confirmed Staphylococcus cohnii. Conclusion: Arachnoiditis is a common pathology with multiple causes. However, isolated bacterial arachnoiditis is rare and has not been mentioned in literature before to our knowledge. We present a case of arachnoiditis proven to be bacterial by tissue culture from the thickened arachnoid layer we took during the surgery after we exclude all other causes.